2012
DOI: 10.5402/2012/718671
|View full text |Cite
|
Sign up to set email alerts
|

Need for Nucleic Acid Testing in Countries with High Prevalence of Transfusion-Transmitted Infections

Abstract: Introduction. In India, family/replacement donors still provide more than 45% of the collected blood. With increasing voluntary blood donation and the still-prevalent infectious diseases in donors, we need to augment transfusion-transmitted infections (TTIs) testing before use. Our study was aimed to know the seroprevalence of TTIs among the donors of Rajasthan and the need for newer technologies like nucleic acid testing (NAT). Materials and Methods. Enhanced chemiluminescence immunoassay (ECi) was used for d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
28
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 25 publications
3
28
2
Order By: Relevance
“…These were individually tested by procleix ultrio assay for HIV 1, HCV and HBV. Another study from Jaipur reported a combined NAT yield (NAT reactive/seronegative) for HIV, HCV and HBV of 0.034 % in 23,779 donors [25] which is high compared to that reported from other developed countries. In another study conducted in north India, 18,354 donors were tested by both ID-NAT and fourth generation enzyme-linked immunosorbent assay (ELISA), 7 were found to be NAT-positive but ELISAnegative (NAT yield) for HBV and HCV.…”
Section: Discussionmentioning
confidence: 82%
“…These were individually tested by procleix ultrio assay for HIV 1, HCV and HBV. Another study from Jaipur reported a combined NAT yield (NAT reactive/seronegative) for HIV, HCV and HBV of 0.034 % in 23,779 donors [25] which is high compared to that reported from other developed countries. In another study conducted in north India, 18,354 donors were tested by both ID-NAT and fourth generation enzyme-linked immunosorbent assay (ELISA), 7 were found to be NAT-positive but ELISAnegative (NAT yield) for HBV and HCV.…”
Section: Discussionmentioning
confidence: 82%
“…The NAT yield rate from other blood Centers in India is 1 in 753, 16 1 in 610, 17 1 in 1528, 18 1 in 2622, 19 1 in 2000, 20 and 1 in 2972. 15 The higher NAT yield compared to other studies 15,18,19,20 is probably on account of higher prevalence in the population reaching to this tertiary care hospital.…”
Section: Discussionmentioning
confidence: 43%
“…Most populations in resource limited countries suffer from high prevalence of transfusion transmitted infections and are expected to have more frequent incident and occult cases. 15 Of the 16551 seronegative donor's samples subjected to NAT testing, there were 17 NAT yields (1 in 974). The NAT yield rate from other blood Centers in India is 1 in 753, 16 1 in 610, 17 1 in 1528, 18 1 in 2622, 19 1 in 2000, 20 and 1 in 2972.…”
Section: Discussionmentioning
confidence: 99%
“…The highest yield was for HBV infection (6/8) [9]. There are a few other reports from India [10][11][12][13][14][15] which also show that the addition of tests to detect nucleic acids (NAT or PCR) increased the yield of donors who are hepatitis B positive. In China and Taiwan, with a high endemicity of hepatitis B, the addition of NAT increased the detection of occult carriers [16,17].…”
mentioning
confidence: 99%
“…In countries where the prevalence of HBV infection is low, minipool strategy is adequate while in high-prevalence countries to which India belongs, individual donor testing is recommended [10,18]. There has been considerable debate regarding the necessity to make NAT mandatory in all blood banks but the significant increase in the cost of NAT tested blood is possibly the major factor which has prevented implementation across all sectors.…”
mentioning
confidence: 99%